The effect of weight loss and exercise on Health-Related Quality of Life (HRQOL) following Endoscopic Bariatric Therapies (EBT) for obesity - Gontrand Lopez-Nava; Ravishankar Asokkumar; T. Lacruz; A. Rull; L. Beltran; Inmaculada Bautista-Castaño (Health and Quality of Life Outcomes, 2020)
Abstract Introduction Endoscopic bariatric therapies (EBT) have demonstrated to induce weight loss and improve comorbidities in obese patients. However, little is known about its impact on health-related quality of life (HRQOL) outcomes and physical activity status. This study aimed to evaluate the change in HRQOL and physical activity following EBT induced weight loss in obese patients. Methods We approached 181 patients who underwent EBT in a standardized multidisciplinary follow-up program to participate in the study. We provided them two questionnaires-a) Short Form-36 health survey with the physical (PSC) and mental (MSC) summary component scores to capture generic HRQOL, and b) international physical activity questionnaire (IPAQ) for physical activity (PA). We administered the survey at baseline and at 9 months post-procedure. We expressed the procedure outcome as percentage total body weight loss (%TBWL). We expressed continuous variables as mean (SD) or median and categorical variables as percentages. We used non-parametric tests for comparison and performed multivariable linear regression analysis to identify factors associated with improvement in HRQOL. Results The mean age was 42.2 (11.3) years, and the mean BMI was 38 (5.9)kg/m2. A majority of them were female (n-132, 73%). The EBT included intragastric balloons (n-136, 75%) and endoscopic sleeve gastroplasty (n-24, 25%). The mean %TBWL achieved after the intervention was 16.9 (9.7)%. We noticed a significant improvement in the median PSC (77.8 vs. 90.4, p < 0.001) and MSC (67 vs. 80.2, p < 0.001) scores after EBT. Similarly, we observed a significant positive change in physical activity compared to baseline (1606.2 vs. 2749 MET-minutes/week, p = < 0.001). Linear regression analysis showed an increase in %TBWL was associated with significant improvement in PSC (β = 0.193, p = 0.003) and MSC (β = 0.166, p = 0.02) scores of HRQOL, and likewise, increase in PA was independently associated with improvement in MSC (β = 0.192, p = 0.01). We did not find any difference in outcome based on gender or the type of intervention. Conclusion EBT improves HRQOL in obese patients regardless of the type of intervention. The weight loss induced by EBT and the improvement in PA positively influence the health outcomes and quality of life.